2015
DOI: 10.1177/0300060515569287
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thioctic acid on allodynia in a rat vincristine-induced neuropathy model

Abstract: Objective: To investigate the antiallodynic effects of thioctic acid in vincristine-induced neuropathy in rats. Methods: Neuropathy was induced in Sprague-Dawley rats via vincristine intraperitoneal injection. After 15 days, rats were investigated for the presence of mechanical and cold allodynia, and those with allodynia received intraperitoneal injection with normal saline or 1, 5, or 10 mg/kg thioctic acid. Mechanical and cold allodynia were assessed before treatment and at 15, 30, 60, 90, 150 and 180 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…All these data suggested a prominently active role of the dextrorotatory enantiomer in the racemic mixture. Accordingly, previous studies on chemotherapyinduced neuropathy described similar results: thioctic acid acutely dosed to vincristine-treated rats reversed allodynia symptoms; chronic injections of 15, 30, and 60 mg/kg of (+/−)-thioctic acid on neuropathic rodents, which were given paclitaxel, significantly reduced mechanical and cold allodynia (Kahng et al, 2015;Sun et al, 2019). As previously reported (Tomassoni et al, 2013), SHR rats showed higher values of systolic blood pressure as compared to WKY rats.…”
Section: Discussionsupporting
confidence: 80%
“…All these data suggested a prominently active role of the dextrorotatory enantiomer in the racemic mixture. Accordingly, previous studies on chemotherapyinduced neuropathy described similar results: thioctic acid acutely dosed to vincristine-treated rats reversed allodynia symptoms; chronic injections of 15, 30, and 60 mg/kg of (+/−)-thioctic acid on neuropathic rodents, which were given paclitaxel, significantly reduced mechanical and cold allodynia (Kahng et al, 2015;Sun et al, 2019). As previously reported (Tomassoni et al, 2013), SHR rats showed higher values of systolic blood pressure as compared to WKY rats.…”
Section: Discussionsupporting
confidence: 80%
“…To confirm the establishment of the vincristine-induced pain model, the 50% PWT and PWL to the radiant heat stimulation were measured prior to vincristine administration and on days 1, 3, 7, 10, 14, and 21 post-administration. Consistent with previous reports ( 17 , 20 ), the results demonstrated that rats in the vincristine-treated group exhibited significant mechanical allodynia and thermal hyperalgesia ( Fig. 1 ).…”
Section: Resultssupporting
confidence: 92%
“…All animal experimental procedures were conducted in accordance with the guidelines of the International Association for the Study of Pain ( 20 ) and were approved by the Animal Experimentation Ethics Committee (AEEC) of Henan University (Kaifeng, China). Vincristine was used to induce neuropathy as previously described ( 20 ). Briefly, 75 µg/kg of vincristine sulfate (Hospira, Lake Forest, IL, USA) was administered once daily intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Vincristine sulphate was used to induce neuropathy as described by Kahng 26 with a little modification. VCR was dissolved in its solvent ampoule, which contained 10 ml sodium solution 0.9% and benzyl alcohol 0.9% with the dosage calculated on daily body‐weight at the dose of 0.1 mg/kg, every other day, in course of the study for 14 days.…”
Section: Methodsmentioning
confidence: 99%